First total synthesis of cyclodepsipeptides clavatustide A and B and their enantiomers. Issue 66 (28th June 2016) - Chettu, Suresh Kumar; Madhu, Rajesh Bagepalli; Raolji, Gajendrasinh Balvantsinh; Babu, Korupolu Raghu; Rao, N. S. Kameswara; Gopalakrishnan, Srividya; Ismail, Ayesha; Reddy, G. Bhanuprakash; Shafi, Syed
Abstract : The enantiopure synthesis of clavatustides A (1 ) and B (3 ) were accomplished by a seven step synthetic protocol starting from commercially available ( R )-phenyllactic acid. Abstract : The enantiopure synthesis of clavatustides A (1 ) and B (3 ) were accomplished by a seven step synthetic protocol starting from commercially available ( R )-phenyllactic acid. As the optical rotation values of synthetic ( R )-clavatustides A and B were not in agreement with the reported values, the corresponding antipodes2 and4 were synthesized from ( S )-phenyllactic acid to address the issue. Both ( R ) and ( S ) clavatustides A and B were evaluated for their anti-proliferative activity against three human cancer cell lines using MTT assay. The cervical cancer cell line (HeLa) was found to be most sensitive to the test compounds in decreasing the cell viability. S -Isomers (2 and4 ) were found to exhibit better anti-proliferative activity when compared to their enantiomers ( R -isomers) with IC50 s 24.5 and 26.8 μM respectively against HeLa cell lines. All the compounds tested had a minimal effect on the cell viability of normal lung cells, indicating that these compounds are not toxic to normal cells.